New Botanical Anxiolytics for Use in Companion Animals and Humans - Liu, Rui (2017)
As part of our ongoing research into botanical therapies for anxiety disorders, the neotropical vine Souroubea sympetala was chosen for study as a phytochemical discovery strategy focusing on rare Central American plant families. When orally administered to male Sprague-Dawley rats, the crude plant extract, its ethyl acetate fraction, supercritical carbon dioxide fraction, or its isolated triterpenes reduced anxiety and/or fear-related behavior in standardized behavioral models. Pharmacological studies showed that the extracts acted at the benzodiazepine GABAA receptor and reduced corticosterone levels. A preparation containing Souroubea fortified with a second triterpene containing plant, Platanus occidentalis, was shown to be safe in a 28-day feeding trial with beagles at 5 times the intended dose. Subsequent trials with beagles in a thunderstorm model of noise aversion showed that the material reduced anxiety behaviors and cortisol levels in dogs. The formulation has been released for the companion animal market in Canada and the USA under the Trademark "Zentrol". Ongoing research is exploring the use of the material in treatment of anxiety and post-traumatic stress in humans.